Improving the Quality of Education Through the Implementation of Cambridge Curriculum: Examining the Advantages, Problems, and Optimization Efforts at SMPI Al Abidin Surakarta - Riza, Muhammad; Selamet, Isnandar; Pramudya, Ikrar (KnE Social Sciences, 2025)
In Indonesia, many schools are beginning to implement international curricula such as the Cambridge curriculum in an effort to improve school quality, This study aims to review the advantages of the implementation of the Cambridge curriculum at SMPI Al Abidin Surakarta and find out the obstacles it faces and the solutions it can find. This research uses a qualitative approach using interview techniques, observation, and documentation as data collection tools. The results indicate that the implementation of the Cambridge curriculum can improve the English language skills of both teachers and students. In addition, students have a deeper understanding of mathematical concepts because the learning approach encourages conceptual understanding before applying procedures or formulas. However, there are also difficulties in the implementation of this curriculum, especially since the language of instruction is English and not all students are proficient. To overcome these difficulties, teachers can provide additional support to strengthen students’ vocabulary or emphasize explanations in Indonesian.